Facilitating flexible learning: A study of students’ perceptions of synchronous and asynchronous blended learning - Susiyawati, Enny; Erman, Erman; Astriani, Dyah; Rahayu, Dwi Anggoro (Journal of Education and e-Learning Research, 2024)
This study explored students’ perceptions of the implementation of synchronous and asynchronous blended learning. The current case study investigated 78 undergraduates who enrolled in a course while involved in an experiential learning program called Merdeka Belajar-Kampus Merdeka (MBKM) or independent learning on an independent campus. Quantitative and qualitative data were collected in this study using surveys and interviews. The quantitative information was analyzed using descriptive statistics whereas thematic analysis was adopted to analyze the qualitative data. The five dimensions of flexible blended learning, including place, time, service, technology and pedagogy were adopted as a framework for this study. The findings suggested that synchronous and asynchronous blended learning could provide flexible learning regarding place, time, service, technology and pedagogy to support students’ learning and participation in the MBKM program. According to students, facilitating factors for the flexibility of synchronous and asynchronous blended learning include providing accessible learning materials, the possibility of time negotiation, providing various ways for social interactions, aligning topics or activities between the course and the MBKM program, small group settings, giving clear feedback and minimal scheduling changes. These factors must be considered when optimizing synchronous and asynchronous blended learning implementations.